ANALISIS KINERJA BPR SYARIAH DI JAWA TIMUR: STUDI KASUS SEBELUM DAN SESUDAH PANDEMI COVID-19 - Ubaidillah, Muhammad Irfan; Al Muizzuddin Fazaalloh (Islamic Economics and finance in Focus, 2024)
The Covid-19 pandemic in Indonesia has had a noticeable impact on the economy, including the profitability of the Islamic People's Financing Bank (BPRS) in East Java, which provides financing to the public. The objective of this research is to determine the impact of Covid-19 on the profitability of Islamic BPRs in East Java, with a sample of 19 Islamic BPRs from the period 2017-2023, using panel data regression analysis techniques. The results of the conducted tests indicate that non-performing financing (NPF) has a negative but insignificant impact on profitability, while operating expenses (BOPO) have a significant negative impact on profitability. Financing-to-deposit ratio (FDR) has a significant positive impact on profitability, while capital adequacy ratio (CAR) has a positive but insignificant impact on profitability. Moreover, Covid-19 has a significant positive impact on the profitability of Islamic BPRs in East Java.